EXPORT FLOOR PRICES IN COCONUT PRODUCTS SRI LANKA EXPERIENCE - R. MALIGASPE (International Coconut Community, 1986)
Export Floor Prices for Coconut Products appear to have been introduced in Sri Lanka initially in the late 1960s. Maximising of foreign exchange earnings and prevention of under‑invoicing by shippers especially under a tight trade and exchange system at that time and also possible expectation of higher proceeds to millers and coconut producers, appear to have been the main considerations when Export Floor Prices were introduced for most of these Products.